Managing risk in commercial-off-the-shelf based space hardware systems - Herbert, Eric W., author; Bradley, Thomas, advisor; Sega, Ronald, advisor; Herber, Daniel, committee member; Shahroudi, Kamran, committee member; Wise, Daniel, committee member (Colorado State University. Libraries, 2024)
The space industry is experiencing a dynamic renaissance. From 2005 to 2021, the industry has exhibited a 265% increase in commercial and government investment [1]. The demand is forecasted to continue its upward trajectory by an added 55% by 2026 [1]. So, the aerospace industry continually seeks innovative space hardware solutions to reduce cost and to shorten orbit insertion schedules. Using Commercial-Off-the-Shelf (COTS) components to build space-grade hardware is one method that has been proposed to meet these goals. However, using non-space-grade COTS components requires designers to identify and manage risks differently early in the development stages. Once the risks are identified, then sound and robust risk management efforts can be applied. The methods used must verify that the COTS are reliable, resilient, safe, and able to survive rigorous and damaging launch and space environments for the mission's required longevity or that appropriate mitigation measures can be taken. This type of risk management practice must take into consideration form-fit-function requirements, mission objectives, size-weight-and-performance (SWaP) constraints, how the COTS will perform outside of its native applications, manufacturing variability, and lifetime expectations, albeit using a different lens than those traditionally used. To address these uncertainties associated with COTS the space industry can employ a variety of techniques like performing in-depth component selections, optimizing designs, instituting robust stress screening, incorporating protective and preventative measures, or subjecting the hardware to various forms of testing to characterize the hardware's capabilities and limitations. However, industrial accepted guidance to accomplish this does not reside in any standard or guide despite space program policies encouraging COTS use. One reason is because companies do not wish to reveal their proprietary methods used to evaluate COTS which, if broadcast, could benefit their market competition. Another is that high value spacecraft sponsors still cling to low-risk time consuming and expensive techniques that require the use of space hardware built with parts that have historical performance pedigrees. Keeping this data hidden does not help the space industry, especially when there is a push to field space systems that are built with modern technologies at a faster rate. This is causing a change in basic assumptions as stakeholders begin to embrace using parts from other industries such as the automotive, aviation, medical, and the like on a more frequent basis. No longer are COTS relegated to use in CubeSats or research and development spacecraft that have singular and limited missions that are expected to function for a brief period. This is because COTS that are produced for terrestrial markets are equally as dependable because of the optimized manufacturing and quality control techniques that reduce product variability. This increases the use of COTS parts in space hardware designs where until recently space programs had dared not to tread. But using COTS does come with a unique set of uncertainties and risks that still need to be identified and mitigated. Despite legacy risk management tools being mature and regularly practiced across a diverse industrial field, there is not a consensus on which risk management tools are best to use when evaluating COTS for space hardware applications. However, contained within technical literature amassed over the last twenty-plus years there exists significant systems engineering controls and enablers that can be used to develop robust COTS-use risk management frameworks. The controls and enablers become the basis to identify where aleatory and epistemic uncertainties exist within a COTS-based space system hardware design. With these statements in mind, unique activities can be defined to analyze, evaluate, and mitigate the uncertainties and the inherent risks to an acceptable level or to determine if a COTS-based design is not appropriate. These concepts were explored and developed in this research. Specifically, a series of COTS centric risk management frameworks were developed that can be used as a roadmap when considering integrating COTS into space hardware designs. From these frameworks unique risk evaluation processes were developed that identified the unique activities needed to effectively evaluate the non-space grade parts being considered. The activities defined in these risk evaluation processes were tailored to uncover as much uncertainty as possible so that appropriate risk mitigation techniques could be applied, design decisions could be quickly made from an informed perspective, and spacecraft fielding could be accomplished at an accelerated rate. Instead of taking five to ten years to field a spacecraft, it can now take less than one to three years. Thus, if effectively used, COTS integration can be a force multiplier throughout the space industry. But first, the best practices learned over the last few decades must be collected, synthesized, documented, and applied. To validate the risk frameworks discussed, a COTS-based space-grade secondary lithium-ion battery was chosen to demonstrate that the concepts could work. Unique risk evaluation activities were developed that took into consideration the spacecraft's mission, environment, application, and lifetime (MEAL) [2] attributes to characterize the battery's COTS cells, printed circuit board, electrical design, and electrical-electronic-electromechanical (EEE) performance, strengths, and weaknesses. The activities defined and executed included risk evaluation activities that included a variety of modeling, analyses, non-destructive examinations, destructive physical assessments, environmental testing, worst case scenario testing, and manufacturing assessments. These activities were developed based on the enablers and controls extracted from the data that was resident in the literature that was reviewed. The techniques employed proved quite successful in uncovering and mitigating numerous aleatory and epistemic uncertainties. The mitigation of these uncertainties significantly improved the battery's design and improved the battery's performance. As a result, the COTS-based battery was successfully built, qualified, and flown on a fleet of launch vehicles and payloads. The information that follows documents how the risk management frameworks were created, what influenced its architecture, and how these were successfully validated. Validating the COTS centric risk management framework was important because it demonstrated the risk management frameworks' utility to uncover uncertainty. It also proved that methods exist that can be readily employed that are not typically within the scope of traditional space hardware design and qualification techniques. This is important because it provides the industry a new set of systems engineering tools that can be employed to limit the impact of supply chain constraints, reduce reliance on expensive low-yield hardware procurement practices, and minimize the amount of obsolete hardware in designs which tend to constrain the space system hardware's performance. As a result, the techniques developed in this research start to fill a gap that exists in the space industry's systems engineering toolbox.
Keywords: risk; uncertainty; space; COTS